A qualitative analysis of psychological distress in hidradenitis suppurativa. (1st February 2020) - Keary, E.; Hevey, D.; Tobin, A.M.
Summary: Background: Hidradenitis suppurativa (HS) can negatively impact on patients' quality of life and is associated with a higher risk of depression, as well as difficulties in employment and relationships. Objectives: This study sought to evaluate the lived experience of psychological distress in HS. Methods: Structured interviews were conducted with 12 participants. These were later transcribed and analysed using thematic analysis. The transcripts and analysis were reviewed by an independent researcher. Results: The results indicated that there were three main themes: shame, pain and coping mechanisms. Participants indicated that their feelings of shame were due to disgust at their symptoms. They feared that others would be disgusted if their symptoms were obvious. Participants reported feeling invalidated when others did not understand the severity of their pain. Additionally, they reported that pain left them with a sense of powerlessness over their own bodies. Regarding coping mechanisms, adaptive strategies included social support while maladaptive strategies included social withdrawal. Conclusions: These findings are discussed in the context of the existing research on shame, chronic pain and psoriasis. The implications for psychological support for individuals with HS are evaluated. Additionally, the limitations of this study are considered and recommendations for future research are given. This study has highlighted that feelings of shame and physical pain are associated with psychological distress in HS. What's already known about this topic? Hidradenitis suppurativa (HS) has been shown to be associated with physical pain, a higher risk of depression, difficulties in sustaining employment and difficulties in relationships. Additionally, studies using quality‐of‐life measures have found more impairment in HS than in other dermatological conditions. What does this study add? Although the research to date has determined that there are negative social and emotional consequences associated with HS, the psychological processes underlying these impairments have not yet been looked at. This study aims to get a deeper understanding of the lived experience of psychological distress in HS and how individuals with HS attempt to manage this distress. What are the clinical implications of the work? This study has identified shame as a key feature that underlies the psychological difficulties experienced as a consequence of HS. When deciding upon appropriate psychological interventions for HS, approaches that specifically focus on reducing feelings of shame should be considered.